UNGKAPAN PUJIAN DALAM FILM ME BEFORE YOU KARYA JOJO MOYES : SUATU ANALISIS PRAGMATIK - DAROMES, SRI WAHYUNI SEPRIANI; JANSEN, FRIEDA TH.; LOTULUNG, DONALD R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis research entitled â€œCompliment Utterances in The Film Me Before You by Jojo Moyes : Pragmatic Analysisâ€. The aims of this research is to identify, classify and analyze the compliment utterances and their function in Me Before You film. This research used a descriptive method. The data were collected from conversation among characters, then they classified and analyzed they are according to the concept of Holmes (1986).The result shows five types of compliment utterances and their function applied by the characters in their dialogues. First, ability consists of 7 compliment utterances based on compliment abilities that function to express solidarity and admiration for abilities that are real. Second, possession consist of 10 compliment utterances based on compliments of possession that serves to express an admiration for human property that is real deserves compliment or appreciation. Third, physical appearance consist of 8 compliment utterances the function of expressing a sense of attraction will fascinate the physical appearance who intends to give real compliment without the desire to mock that can establish a smooth and positive communication relationship. Fourth, personality consist of 22 compliment utterances based on personality compliment that serves to express a sense of solidarity, admiration, appreciation of the behaviour, character, or nature of someone who can build one's self-confidence. Fifth, quality consist of 3 compliment utterances based serves to express a sense of appreciation for someone good and bad qualities. This compliment phrase also serves to appreciate the actions or qualities produced by someone who can build one's enthusiasm. Keywords : Compliment utterances, Film : Me Before You, Pragmatic Analysis